Empowering MSMEs with Basic Accounting Skills for Effective Financial Management - Djatnicka, Erlina Widayanti; Purba, Jamian; Wulandari, Dian Sulistyorini; Lutfi, Adilista Puspa Aliya (PT FORMOSA CENDEKIA GLOBAL, 2024)
This community service program aimed to enhance the financial literacy of small and medium-sized enterprises (MSMEs) in Cikarang Pusat. The initiative sought to equip MSMEs owners with fundamental accounting skills necessary for better financial management, focusing on creating financial statements, budgeting, expense tracking, and analyzing financial data. Throughout the program, participants were trained through practical workshops that provided hands-on experience with financial tools and techniques. Pre- and post-program assessments showed a significant increase in participants' confidence levels in managing their business finances, with a marked decrease in those reporting very low or low confidence and an increase in those rating their confidence as high. The program's success highlights the importance of financial education for MSMEs in promoting business sustainability and growth. Based on the results, the program recommends further education, the integration of digital financial tools, and the establishment of peer learning networks to support the ongoing financial development of MSMEs owners. This initiative demonstrates the value of community-based educational efforts in strengthening the financial capabilities of local businesses.